213. Pre-treatment verification of stereotactic plans using a bi-dimensional diamond detector. (December 2018) - Talamonti, C.; Bartoli, A.; Scaringella, M.; Baldi, A.; Masi, L.; Pallotta, S.; Bruzzi, M.
Abstract : Purpose: The aim of this study is to test the performance of a new bi-dimensional diamond dosimeter, manufactured within the DIAPIX and IRTP Italian INFN projects, in pre-treatment verification of high conformal plans. Methods: DIAPIX dosimeter consists of two pCVD diamond matrices (12 × 12 pixels, 2 mm pitch) coupled together covering a total area 2.5 × 4.8 cm 2 with 1 mm dead space between matrices[1] . Dosimetric verifications of lung plans delivered with Cyberknife (CK) and 6 MV photon Elekta Synergy BM (EBM) were compared with the plans calculated with Multiplan Cyberknife and Monaco Elekta TPS. Since some pixels, mainly concentrated in a single matrix, were not fully operational, two measurements in gun-target and three in latero-lateral directions were necessary to cover the full EBM planning area. Bad pixels in both matrices were masked and they were assigned the average value of neighbour pixels and a global 3 × 3 pixel filter was applied. Dose distributions were registered with intensity-based algorithms and γ -index was evaluated with an in-house developed MATLAB routine and focused on the best performing matrix. The passing rate ( γ < 1 ) was evaluated for 3%/3 mm criteria. Results: CK passing rate over the whole dosimeter was 72% and for the EBM was 77%. These values increase to 84% and 85% for CK and EBM respectively just selecting the best performing matrix (Fig. 1). Moreover γ analysis showed that pixels corresponding to the edge of the matrix have a different behaviour and excluding them the passing rate increases to 93% for CK and 95% for EBM. Conclusions: DIAPIX, a bi-dimensional pCVD diamond detector was tested with CK and EBM plans. Its intrinsic characteristics and performance make the DIAPIX pCVD diamond matrix a very innovative and promising technology to be used for pre-treatment verification of stereotactic plans. Future plans are focused on improving pixel contacts to get better device performance and uniformity.